Bike battles : a history of sharing the American road - Longhurst, James (University of Washington Press, 2015)
Americans have been riding bikes for more than a century now. So why are most American cities still so ill-prepared to handle cyclists? James Longhurst, a historian and avid cyclist, tackles that question by tracing the contentious debates between American bike riders, motorists, and pedestrians over the shared road.